Diffusing gender equality norms in the midst of a feminicide pandemic: The case of AMEXCID and decentralized Mexican South-South cooperation. (April 2018) - Sørensen, Ninna Nyberg
Mexican development policy is guided by the country's dual function as both a recipient and a provider of international cooperation. Over the past 17 years, the country has taken several initiatives to promote gender equality nationally, and today gender equality norms cut across Mexican priorities in foreign policy and South-South cooperation activities. Paradoxically, the gains achieved at policy formulating tables have been accompanied by a rise in gender-based violence. To approach this paradox, this article engages with gender equality norms to show how they have been introduced, developed and transformed in the context of a national security crisis and extreme violence directed at women. The analysis points to the important role of Mexican feminists and anti-feminicide activists in the promotion of gender equality norms, as well as to the existence of a political landscape in which structural inequality persists and such norms remain highly contested.